The Business of Electing a President - Erik Hieta (European Journal of American Studies)
This article discusses campaign finance as a cultural phenomenon and how it became bound up with celebrity politics and popular perceptions of elitism. It further explores how the rhetorical function of money became so central to the popularization of politics in the last election. The central argument is that cultural shifts in the way voters viewed the links between money and government account for their rejection of the political status quo. Social media popularized the rhetoric of money as never before. The article highlights the links between money and pop politics, focusing on the uniqueness of the election; super PACs, dark money, and a lack of trust in Washington; campaign finance and the frayed nature of party politics; and general perceptions about money and political corruption. Finally, it addresses the troubling and unprecedented mixing of Donald Trump’s presidency and his business and the broader ramifications of such a polarizing presidential election.